The Influence of the Discovery Learning Model in Improving Students' Critical Thinking Skills on Elasticity Material - Rizka Nurul Atmi Aulia; Gunawan Gunawan; Sutrio Sutrio (Indonesian Journal of STEM Education, 2025)
This research aims to find out and find the effect of the discovery learning model in improving students’ critical thinking skills on elasticity material. This research was carried out at SMAN 1 Sukamulia. The type of research used was quasi-experimental with a nonequivalent control group research design. The population in this study was all students in class XI MIPA for the 2024/2025 academic year, totaling 2 classes. Meanwhile, the sample for this research was class XI MIPA 1 as an experimental class with a total of 30 students. Meanwhile, XI MIPA 2 is the control class with 25 students selected using purposive sampling techniques. The instrument used is a written test in the form of a description (essay) with a total of 6 questions that have been tested. The results of this research show that the average value for the experimental class is 62.86 and the control class has an average of 54. The results of the hypothesis test show that both classes are homogeneously and normally distributed. By using the t-test pollet variance formula, t(calculation) is 2.15 and t(table) is 2.02 so that t(calculation) is greater than T(table), then Ho is rejected and ha is accepted, thus it can be concluded that there is The influence of the discovery learning model in improving students’ critical thinking skills on elasticity material.